1996
DOI: 10.1016/0024-3795(95)00095-x
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial maps with strongly nilpotent Jacobian matrix and the Jacobian conjecture

Abstract: Let H : k n → k n be a polynomial map. It is shown that the Jacobian matrix JH is strongly nilpotent (definition 1.1) if and only if JH is linearly triangularizable if and only if the polynomial map F = X +H is linearly triangularizable. Furthermore it is shown that for such maps F sF is linearizable for almost all s ∈ k (except a finite number of roots of unity).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…The Jacobian matrix matrix J(F ) was called strongly nilpotent if all products of n matrices of the form J(F )(a i ), for possibly distinct points a i ∈ R n , are zero. In [23] the Jacobian matrix of a polynomial map F : k n → k n was defined to be strongly nilpotent if the matrix product J(F )(a 1 )J(F )(a 2 ) · · · J(F )(a n ) is zero, where the a i are distinct sequences of independent variables of length n (that is, "generic points"). If k is infinite, this is equivalent to the obvious generalization of the first definition to k. The following somewhat more general definition can be used in both these cases.…”
Section: Strong Nilpotencementioning
confidence: 99%
“…The Jacobian matrix matrix J(F ) was called strongly nilpotent if all products of n matrices of the form J(F )(a i ), for possibly distinct points a i ∈ R n , are zero. In [23] the Jacobian matrix of a polynomial map F : k n → k n was defined to be strongly nilpotent if the matrix product J(F )(a 1 )J(F )(a 2 ) · · · J(F )(a n ) is zero, where the a i are distinct sequences of independent variables of length n (that is, "generic points"). If k is infinite, this is equivalent to the obvious generalization of the first definition to k. The following somewhat more general definition can be used in both these cases.…”
Section: Strong Nilpotencementioning
confidence: 99%
“…[7] showed that a polynomial map F = X + H is linearly triangularizable if and only if JH is strongly nilpotent, i.e., JH Y 1 JH Y 2 · · · JH Y n = 0 for vector variables Y 1 Y n . By this result, we may determine whether F is linearly triangularizable in each case by checking that whether JH is strongly nilpotent.…”
Section: The General Casementioning
confidence: 99%
“…It is shown that the Jacobian of non-Keller mapping being constant must vanish. It is a new mapping unlike with Keller maps that were studied over the last fifteen years [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%